EFFECTIVENESS OF GIVING A COMBINATION OF BOILED BASIL LEAVES (OCIMUM BASILICUM) AND GINGER (ZINGIBER OFFICINALE) IN REDUCING PAIN FROM PRIMARY DYSMENORRHEA IN ADOLESCENT GIRLS - Eti kuswandari; Sayuti; Mufida Annisa R; Woro Tri Utami (Institut Ilmu Kesehatan Nahdlatul Ulama Tuban, 2026)
Background: Primary dysmenorrhea is a common issue among adolescent girls, characterized by lower abdominal pain due to excessive uterine contractions. Non-pharmacological management using herbal ingredients such as basil leaves (Ocimum basilicum) and ginger (Zingiber officinale) serves as an alternative due to their flavonoid and gingerol content, which function as natural analgesics and anti-inflammatories. Method: This quasi-experimental study used a pretest-posttest control group design. The sample consisted of 30 adolescent girls aged 19–23 years in Junrejo Village, selected via purposive sampling. The intervention group received a combination of basil leaf and ginger decoction, while the control group received a placebo. Pain scale was measured using the Numeric Rating Scale (NRS). Data were analyzed using the Wilcoxon and Mann-Whitney tests. Results: Univariate analysis showed that prior to the intervention, the majority of respondents experienced moderate dysmenorrhea pain (70.0%). After administering the combination of basil leaf and ginger decoction, the majority experienced a decrease in pain intensity to the mild category (63.3%), with no respondents remaining in severe pain. The Wilcoxon Signed Rank Test demonstrated a significant decrease in the mean pain scale from 5.20 to 1.83 (p = 0.000). These findings indicate that the decoction is highly effective in reducing primary dysmenorrhea pain. Conclusion: The combination of basil leaf and ginger decoction is highly effective in reducing primary dysmenorrhea pain intensity in adolescent girls. This herbal remedy is recommended as a safe, economical, and accessible non-pharmacological complementary therapy for independent menstrual pain management.